Plasma rico en plaquetas en el tratamiento de úlceras crónicas - Martínez Pizarro, Sandra (Mediciego, 2020)
Chronic ulcers are a major global health problem with a great impact on a personal, professional and social level. In addition, they involve a high cost in human and material resources. In recent years scientific studies have proposed the use of platelet-rich plasma (PRP) to promote healing.